Sensor technology to monitor health, well-being and movement among healthcare personnel at workplace: a systematic scoping review protocol - Välimäki Maritta; Hipp Kirsi; Chen Jiarui; Huang Xiaoting; Guo Jia; Wong Man Sing (BMJ PUBLISHING GROUP, 2025)
Introduction: The well-being and health of healthcare personnel is becoming increasingly important in the delivery of high-quality healthcare. The recent developments in technology have provided new opportunities for the objective detection of a wide variety of real-world properties and movement. However, technologies that are used to monitor health, well-being and movement among healthcare personnel have not been fully synthesised. The overall aim of this scoping review is to examine what type of sensor technology is available to monitor the health, well-being and movement of healthcare personnel in healthcare settings. More specifically, we want to explore what types of sensor technology applications, for what purposes and how they have been used to monitor health, well-being and movement among healthcare personnel in different workplace settings.
Methods and analysis: This scoping review protocol will follow Arksey and O'Malley's methodology, complemented by the approach of the Joanna Briggs Institute to scoping reviews and guidance for conducting systematic scoping reviews. Peer-reviewed literature will be identified using a search strategy developed by a librarian, and a wide range of electronic datasets of medical, computer and information systems disciplines will be used. Eligibility of the articles will be determined using a two-stage screening process consisting of (1) a title and abstract scan, and (2) a full-text review. Extracted data will be thematically analysed and validated by an expert of sensor technology and a group of nurses as stakeholders. Descriptive statistics will be calculated when necessary.
Ethics and dissemination: The results obtained from the review will inform what technology has been used, how it has been used in healthcare settings and what types of technology might still be needed for future innovations. Findings of the scoping review will be published in a peer-reviewed journal.